DEVELOPMENT OF THE INTERNATIONALIZATION "ABROAD" IN POLISH AND UKRAINIAN HIGHER EDUCATION - Marta Tutko; Tetiana Golubieva (Jesuit University Ignatianum in Krakow, 2016)
The scientific goal of the paper is to present the issue of the development of internationalization "abroad" in Polish and Ukrainian higher education. The leading research method is a comparative method, specifically the method of international comparison. The authors focus on the national and institutional level comparison of the development of internationalization "abroad" in Polish and Ukrainian higher education systems. In addition to the comparative method, the authors applied the method of secondary research (desk research), the method of description and analysis and critique of the scientific literature. By using the source materials and indicated numerical data, it is possible to verify the thesis. The process of reasoning in the article was conducted in the following stages. First, the definition of internalization in higher education was given with respect to Polish and Ukrainian approach. Next, the stages in the development of internationalization "abroad" in Polish and Ukrainian higher education were featured. Afterwards, the development process of internationalization was presented on the background of processes occurring in the European Higher Education Area. The paper ends with conclusions. The conclusions drawn in the paper allowed to verify the thesis. In both countries, Poland and Ukraine, the diversity of activities in frame of internationalization "abroad" occur. Among these activities mobility of students and academic teachers remain the most visible in Poland as well as in Ukraine. The development of internationalization "abroad" in relation to mobility of projects, programmes and providers seems to be more advanced in Poland.